A case study: Inland Revenue Board of Malaysia (IRBM) in encouraging Malaysian to pay taxes - Sufian Nory, Nor Suhaily; Yasin, Megat Al Imran; Shekh Alsagoff, Syed Agil; Bidin, Rosmiza (Human Resource Management Academic Research Society, 2022)
Appropriate planning, proper execution and continuous evaluation of the communications should be viewed as constitutive. In terms of the framework, the models and concepts, as well as the breadth of strategic communication may be observed. This research is conducted by utilizing a case study technique, which is a qualitative data analysis. As part of the implementation of strategic communication activities within the company, Inland Revenue Board of Malaysia (IRBM) has utilized several models. In this regard, this work seeks to unveil the strategic communication approach used by IRBM to encourage taxpayers for fulfilling their duties in Malaysia; as its organization’s strategies. In terms of communication efficiency and its effects on the organization, strategic communication is thoroughly examined. The objective of this survey is, therefore, to determine the IRBM’s strategy for communication with respect to improving tax compliance in Malaysia. This analysis shows that well-positioned employees, and continuous evaluation platforms are capable of improving fiscal adherence in Malaysia.